2022
DOI: 10.7717/peerj.14480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cleaning sports mouthguards with ethylene-vinyl acetate on oral bacteria

Abstract: Background Sports mouthguards, worn in the oral cavity to prevent sports injuries, are constantly exposed to various microorganisms that cause oral infections. Hence, the optimal cleaning methods for sports mouthguards have been thoroughly examined. In this study, we evaluated the efficiency of cleaning effects with a mouthguard cleaner (MC) on microbial biofilm formation in sports mouthguards in vitro and in vivo. Methods We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In the present study, all groups exhibited values higher than 0.2 μm, indicating that the EVA surface is sufficiently rough for bacterial colonization. This finding emphasizes the necessity of regular daily cleaning for this device, just as other studies have shown 23 . Moreover, the results indicate that the surface roughness does not become more pronounced following these procedures.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, all groups exhibited values higher than 0.2 μm, indicating that the EVA surface is sufficiently rough for bacterial colonization. This finding emphasizes the necessity of regular daily cleaning for this device, just as other studies have shown 23 . Moreover, the results indicate that the surface roughness does not become more pronounced following these procedures.…”
Section: Discussionsupporting
confidence: 75%
“…This finding emphasizes the necessity of regular daily cleaning for this device, just as other studies have shown. 23 Moreover, the results indicate that the surface roughness does not become more pronounced following these procedures.…”
Section: Discussionmentioning
confidence: 90%
“…Maintaining a smooth surface is crucial to ensure adequate hygiene of the MTG. 30,31 Custom-fit MTGs need to properly fit the teeth and soft tissues. 2 This is typically achieved through individualized impression(s) of the maxillary arch and production of the final cast model, which can be performed by conventional or digital techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The irregular internal surface of the MTG can also cause soft tissue irritation and discomfort, making the MTG unfit for use. Maintaining a smooth surface is crucial to ensure adequate hygiene of the MTG 30,31 …”
Section: Discussionmentioning
confidence: 99%